STRUKTUR DAN FISIOGNOMI VEGETASI MANGROVE DI REMPANG CATE KOTA BATAM - Yarsi Efendi; Dahrul Aman Harahap (SIMBIOSA, 2014)
Structure and physiognomy of mangrove strongly influenced by the zonation that occurred in the area of mangroves growth. The differences of zona growth will effect  to differences in the structure and composition of vegetation. There are three zones in the mangrove area, which is caused by the difference of flooding which also resulted in the difference to the salinity. The differences of growth zone will performed to the type vegetation performance (Physiognomy). This study is aims to prove the mangrove’s physiognomy that taken in the coastal area of Rempang Cate  Batam, on March 2014 to June 2014. This study was a survey with data collection using a vertical transect plots 100 m. Based on the research that has been done obtained difference vegetation physiognomy stands for every level of growth in each zone growth. Proximally found 13 species of mangroves in 8 families. The results of the analysis of the vegetation on the trees growth level are, Ceriops decandra have the greatest significance important value 167.55% on sapling (juvenille ) level is dominated by Rhizophora apiculata 120%, and seedling growth level dominated by Rhizophora apiculata  186.80%. Keywords: Structure and physiognomy, mangrove zonation